Invagination of Ectodermal Placodes Is Driven by Cell Intercalation-Mediated Contraction of the Suprabasal Tissue Canopy. - Eleni Panousopoulou; Jeremy B A Green (PLoS Biology)
Ectodermal organs such as teeth, hair follicles, and mammary glands begin their development as placodes. These are local epithelial thickenings that invaginate into mesenchymal space. There is currently little mechanistic understanding of the cellular processes driving the early morphogenesis of these organs and of why they lead to invagination rather than simple tissue thickening. Here, we show that placode invagination depends on horizontal contraction of superficial layers of cells that form a shrinking and thickening canopy over underlying epithelial cells. This contraction occurs by cell intercalation and is mechanically coupled to the basal layer by peripheral basal cells that extend apically and centripetally while remaining attached to the basal lamina. This process is topologically analogous to well-studied apical constriction mechanisms, but very different from them both in scale and molecular mechanism. Mechanical cell-cell coupling is propagated through the tissue via E-cadherin junctions, which in turn depend on tissue-wide tension. We further present evidence that this mechanism is conserved among different ectodermal organs and is, therefore, a novel and fundamental morphogenetic motif widespread in embryonic development.